Tracing the Development of Sabbath’s Understanding Emphasized in Seventh-day Adventist Hymnody from 1849 to 1941 - Glenn Jonathan Jerome Latuni; Glenie Latuni (Clef: Jurnal Musik dan Pendidikan Musik, 2026)
Hymnody has played a significant role in shaping and expressing the theological identity of the Seventh-day Adventist Church, functioning as sung theology that communicates doctrine, worship, and spiritual experience. This study traces the development of the understanding of the Sabbath as reflected in Seventh-day Adventist hymnody from 1849 to 1941. Using a descriptive-historical research approach, this paper analyzes five representative hymnals: Hymns for God’s Peculiar People (1849), Hymns for Second Advent Believers Who Observe the Sabbath of the Lord (1852), Hymns and Tunes for Those Who Keep the Commandments of God and the Faith of Jesus (1869), Christ in Song (1900), and Church Hymnal (1941). The analysis reveals that early Sabbatarian hymnody strongly emphasized the Sabbath as a divine institution, a sign of faithfulness, and an eschatological marker associated with the Seal of God and the Second Coming of Christ. Over time, the emphasis expanded to include practical worship, personal devotion, Christ-centered theology, and spiritual renewal. By 1941, the Sabbath was predominantly portrayed as a sacred day of worship, intimate communion with God, and a foretaste of eternal rest. This study concludes that the development of Adventist hymnody reflects the church’s theological maturation while also revealing a gradual reduction in explicit eschatological Sabbath themes in later hymnals.